2017
DOI: 10.1091/mbc.e16-10-0733
|View full text |Cite
|
Sign up to set email alerts
|

Coupled excitable Ras and F-actin activation mediates spontaneous pseudopod formation and directed cell movement

Abstract: Chemotaxis is the mechanism by which cells move in the direction of chemical gradients. The central circuit connecting basal movement and gradient sensing is unknown. Ras activation and F-actin form one coupled excitable system, which is the beating heart of cell movement in both the absence and presence of external cues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
121
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(139 citation statements)
references
References 56 publications
6
121
0
Order By: Relevance
“…Especially microtubules are discussed as important in this respect [157] [140] [141] [142], representing quantum channels related to consciousness [158] [159] and terahertz oscillations in tubulin were reported to be affected by exposures to anesthetics [160]. Besides microtubules, also the actin filaments behave as excitable medium which transports ionic waves and mediates eukaryotic chemotaxis in response to diverse gradients [161] [162] [163] [164]. Actin cytoskeleton supports lipid rafts, which are ordered domains of biological membranes particularly sensitive to anesthetics [165] [166] [167] [168].…”
Section: Emerging Sources Of Cellular Levels Of Sentience and Consciomentioning
confidence: 99%
“…Especially microtubules are discussed as important in this respect [157] [140] [141] [142], representing quantum channels related to consciousness [158] [159] and terahertz oscillations in tubulin were reported to be affected by exposures to anesthetics [160]. Besides microtubules, also the actin filaments behave as excitable medium which transports ionic waves and mediates eukaryotic chemotaxis in response to diverse gradients [161] [162] [163] [164]. Actin cytoskeleton supports lipid rafts, which are ordered domains of biological membranes particularly sensitive to anesthetics [165] [166] [167] [168].…”
Section: Emerging Sources Of Cellular Levels Of Sentience and Consciomentioning
confidence: 99%
“…We found that Ras/Rap‐ and Rac/actin‐centered networks, STEN and CEN, respectively, interact to control dynamic wave patterns at the cell cortex. Although the components we highlight are only a subset of the overall system (Devreotes et al , ; van Haastert et al , ; Fort et al , ; Li et al , ; Tanabe et al , ), they capture essential features of wave organization. In each network, various components sequentially and coordinately engage in wave propagation.…”
Section: Discussionmentioning
confidence: 99%
“…“Actin waves” were first reported by Vicker in Dictyostelium (Vicker, 2002) and extensively characterized by Gerisch and colleagues (Bretschneider et al, 2004; Bretschneider et al, 2009; Gerisch et al, 2009; Gerisch, 2010; Gerisch et al, 2011; Schroth-Diez et al, 2009). Waves of the biosensors for Ras (Xiong et al, 2010) (van Haastert et al, 2017) and PI3K activation were also observed in cells during migration. Studies of the recruitment of Scar subunits, F-actin binding proteins, and biosensors for Ras, PI3K, and Rac activation and coordinated dissociation of PTEN and myosin from the cell cortex suggest that the entire signal transduction and cytoskeletal networks show this behavior (Supplemental Video 5)).…”
Section: The Signal Transduction “Excitable” Network or Stenmentioning
confidence: 94%
“…Different sensitivities among patches as well as individual cells feed into the dose-response behavior. More sensitive methods have detected smaller, perhaps subthreshold, patches Ras activity that do not expand (van Haastert et al, 2017). Third, refractory periods for chemoattractant and shear force-elicited PIP3 production were demonstrated by applying short, paired stimuli and monitoring the response to the second (Nishikawa et al, 2014; Huang et al, 2013; Artemenko et al, 2016).…”
Section: The Signal Transduction “Excitable” Network or Stenmentioning
confidence: 99%